Determinan Mobilitas Tenaga Kerja Commuter dan Sirkuler di Provinsi Sumatera Barat - Fatimah Azzahra Damanik; Joan Marta (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Commuter and circular labor mobility emerged as a labor adjustment measure in response to the weak economic base in the area of residence in the employment of all residents, in the wage differentials and in the spatial distribution of economic activities. This research aims to see the influence of commuter and circular workforce mobility in West Sumatra Province. This research employs multinomial logistic regression analysis by using data from SAKERNAS 2020. The results of this study indicate that the employment sector, gender and income level have a significant influence on the mobility of commuter and circular labor in West Sumatra Province. Marital status has an insignificant influence on the mobility of commuter and circular labor in West Sumatra Province. Age has an insignificant influence on the mobility of commuter labor and a positive and significant influence on the mobility of circular labor in West Sumatra Province. Education level has a positive and significant influence on the mobility of commuter labor and a negative and insignificant influence on the mobility of circular labor in West Sumatra Province. Area of residence has a negative and significant influence on the mobility of commuter and circular labor.